STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN DISIPLIN GURU DI SDN 2 BADUR KECAMATAN CIRINTEN KABUPATEN LEBAK - Desti Utami Sundari; Taufiqurrahman Taufiqurrahman; Jejen Musfah; Sita Ratnaningsih (Program Studi PGSD Universitas Flores, 2023)
Teacher discipline is the key to the success of educational institutions. In improving teacher discipline, a brave and visionary principal is needed. This study describes the principal's strategy in improving teacher discipline. The location of this research was carried out at SDN 2 Badur, Cirenten Lebak District. The method used in this research is descriptive qualitative with a case study approach. Data collection techniques in this study are through observation, in-depth interviews and documentation. Activities in data analysis are: data reduction, data display, and drawing conclusions/verification. The results of the study show that there are 6 principal strategies in improving teacher discipline, namely: motivational strategies, setting an example, making rules, supervising, giving warnings or punishments, and giving rewards.